Determination of Toxoplasmosis Disease Activity by Estimation of IL-6 Cytokine - K. Al-Zohairy, Lina; N. AL-Qadhi, Ban (Iraqi Journal of Science, 2023)
Toxoplasma gondii (Nicolle and Manceaux ) infects all warm-blooded animals,including humans. Early diagnosis and determining the infective stage are critical fortreating immunosuppressed individuals and pregnant women with toxoplasmosis.This parasite modulates pro- and anti-inflammatory responses to regulate parasitemultiplication and host survival. The aim of this study was to investigate theprobability of using IL-6 as a marker of toxoplasmosis disease activity (acute andchronic) in different groups of women (miscarriage, pregnant and single) and estimatethe relationship between infection and gestational age and history of abortion inmiscarriage and pregnant women. The most abortion were occurred at the firsttrimester in chronic infected miscarriage women also, the most abortion wereoccurred at the first trimester in acute infected pregnant women. The result showedthat acute infected miscarriage women with previously abortion scored highsignificant percentage of infection in comparison to non- abortifacient, chronicinfected one and pregnant women. IL-6 was significantly higher in acute infectedmiscarriage women in comparison to single and pregnant acute one but chronicinfected pregnant women characterized by the lowest level of this cytokine incomparison to all studied groups.